2009
DOI: 10.1097/rct.0b013e31819a60f3
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of the Rectosigmoid Colon

Abstract: Our preliminary findings show that quantitative DWI may be able to differentiate the normal rectum from neoplastic involvement, in addition to distinguishing between inflammatory and neoplastic involvements. However, radiologists should be aware of possible overlaps that may lead to misdiagnoses when DWI is used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…A difference from previous study comes from the inclusion of longer intestinal segments to be assessed. However, the results of the study are similar to those of the earlier study (6) in that they call for further research and requirement of increasing patient population size. Actually, this conclusion is justified because of the overlapping ADC values.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…A difference from previous study comes from the inclusion of longer intestinal segments to be assessed. However, the results of the study are similar to those of the earlier study (6) in that they call for further research and requirement of increasing patient population size. Actually, this conclusion is justified because of the overlapping ADC values.…”
supporting
confidence: 79%
“…It has been known previously that a number of benign lesions can exhibit hyperintensity on DW-MRI with high b-values, (9) and that ADC values in benign and malignant lesions may overlap, which makes it difficult to distinguish lesions using DW-MRI alone. In both studies (2,6), it was emphasized that, radiologists should be aware of possible overlaps of ADC values that may lead to misdiagnoses when only DWI is interpreted.…”
mentioning
confidence: 99%
“…In a small retrospective series, ADC values of the normal rectum and rectosigmoid malignancy groups and rectosigmoid carcinoma and inflammatory bowel disease groups were significantly different (P < 0.01). A cut-off value for carcinomas of 1.14×10 -3 mm 2 /s yielded a sensitivity and specificity of 93.3% and 93.3%, respectively (26). In a recent study, Song et al (23) reported that the mean ADC of the viable tumor group was significantly lower than that of the non-viable tumor group.…”
Section: Discussionmentioning
confidence: 99%
“…In rectal cancer, the applications of DWI include tumor detection, tumor characterization, distinguishing tumor tissue from nontumor tissue, and monitoring and predicting treatment response (3)(4)(5)(6)(7)(8). For local staging of rectal cancer, adding DWI to conventional magnetic resonance imaging (MRI) yields better identification of tumor borders and locoregional lymph nodes than conventional MRI alone (9,10).…”
mentioning
confidence: 99%